Evaluating the Mediating Role of Cognitive Emotion Regulation in the Relationship Between Psychological Capital and Attachment Styles With Risky Behaviors in Lower Secondary School Girls - Bathaei, Seyyedeh Maryam; Davari , Rahim; Ebrahimi Moghaddam, Hossein (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to determine the relationship between risky behaviors based on psychological capital and attachment styles, with the mediating role of cognitive emotion regulation in lower secondary school girls. Methods and Materials: This research is applied in terms of purpose and descriptive-correlational in terms of data collection. The statistical population included all female students studying in lower secondary schools in Tehran during the academic year 2023–2024. A total of 385 participants were selected using a multistage cluster random sampling method. The study employed the Risky Behaviors Questionnaire by Zadehmohammadi et al. (2008), the Psychological Capital Questionnaire by Luthans et al. (2007), the Attachment Styles Questionnaire by Hazan and Shaver (1987), and the Cognitive Emotion Regulation Questionnaire by Garnefski et al. (2001). Data were analyzed using Pearson correlation and structural equation modeling (SEM) through SPSS v27 and LISREL v8.8. Findings: The findings revealed that psychological capital, secure attachment style, and positive cognitive emotion regulation had a significant negative direct effect on risky behaviors. In contrast, avoidant insecure attachment style and negative cognitive emotion regulation had a significant positive direct effect on risky behaviors. The results for the indirect effects showed that the relationship between psychological capital and attachment styles with risky behaviors was significantly mediated by cognitive emotion regulation (P < .05). Conclusion: Based on the findings, understanding the elements that may influence adolescents’ propensity toward risky behaviors is crucial for designing effective intervention strategies to prevent such behaviors.